2022
DOI: 10.3390/ijerph19148586
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of 24-Hour Movement Behaviors with Weight Status and Body Composition in Chinese Primary School Children: A Cross-Sectional Study

Abstract: 24 h movement behaviors, specifically physical activity (PA), sedentary behavior, and sleep, play a crucial role in the prevention and intervention of childhood obesity. This study aimed to examine the association of 24 h movement behaviors with weight status and body composition among Chinese primary school children. Using a random stratified sampling, 978 eligible participants (9.1 ± 1.4 years, 53.2% boys) were recruited from 1 May to 15 July 2021. Demographics included children’s age, gender, grade, parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Regarding obesity‐related indicators, the most common obesity‐related indicators were zBMI [35, 37, 38, 40, 42, 44–47, 49, 55, 56], waist circumference [36, 38, 45, 48, 53, 54, 60], BMI [35, 36, 39, 41, 48, 53, 58], body fat by bioelectrical impedance analysis [57, 62] or dual‐energy x‐ray absorptiometry [38, 55], only obesity [48, 63], and overweight/obesity [35, 37, 41, 43, 46, 50–52, 56, 59, 61–63]. Regarding the measurement of the 24‐hour movement recommendations, physical activity was assessed by accelerometer‐based measures in 17 studies [35, 37, 38, 40, 41, 43, 45, 46, 49, 51–56, 58, 59] and self‐reported measures by young people and parents in 12 studies [36, 39, 42, 44, 47, 48, 50, 57, 60–63]. Screen time was self‐reported by young people in 14 studies [36, 38, 39, 44, 46–48, 50, 54, 56–58, 61, 62] and by parents in 15 studies [35, 37, 40–43, 45, 49, 51–53, 55, 59, 60, 63].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding obesity‐related indicators, the most common obesity‐related indicators were zBMI [35, 37, 38, 40, 42, 44–47, 49, 55, 56], waist circumference [36, 38, 45, 48, 53, 54, 60], BMI [35, 36, 39, 41, 48, 53, 58], body fat by bioelectrical impedance analysis [57, 62] or dual‐energy x‐ray absorptiometry [38, 55], only obesity [48, 63], and overweight/obesity [35, 37, 41, 43, 46, 50–52, 56, 59, 61–63]. Regarding the measurement of the 24‐hour movement recommendations, physical activity was assessed by accelerometer‐based measures in 17 studies [35, 37, 38, 40, 41, 43, 45, 46, 49, 51–56, 58, 59] and self‐reported measures by young people and parents in 12 studies [36, 39, 42, 44, 47, 48, 50, 57, 60–63]. Screen time was self‐reported by young people in 14 studies [36, 38, 39, 44, 46–48, 50, 54, 56–58, 61, 62] and by parents in 15 studies [35, 37, 40–43, 45, 49, 51–53, 55, 59, 60, 63].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the measurement of the 24‐hour movement recommendations, physical activity was assessed by accelerometer‐based measures in 17 studies [35, 37, 38, 40, 41, 43, 45, 46, 49, 51–56, 58, 59] and self‐reported measures by young people and parents in 12 studies [36, 39, 42, 44, 47, 48, 50, 57, 60–63]. Screen time was self‐reported by young people in 14 studies [36, 38, 39, 44, 46–48, 50, 54, 56–58, 61, 62] and by parents in 15 studies [35, 37, 40–43, 45, 49, 51–53, 55, 59, 60, 63]. Sleep duration was determined by accelerometer‐based measures in 9 studies and self‐reported measures by young people and parents in 20 studies [35, 36, 40, 42–45, 47–53, 57, 59–63].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An average medium effect size (Cohen d = 0.54) of PA intervention on FMSs in obese children was proposed based on previous studies [ 32 ]. Considering the minimal class size is 30 and the prevalence rate of childhood obesity is approximately 20% [ 60 ], a cluster size of 6 (for each class) was selected in this study. Using an ICC of 0.01 [ 61 ], an alpha of 0.05, a statistic power of 80%, and an attrition rate of 15% [ 43 ], at least 84 participants in each condition (12 clusters per condition), for a total of 168 participants in 24 clusters will be required for this CRCT.…”
Section: Methodsmentioning
confidence: 99%
“…A Bio-Impedance Analysis (BIA) was conducted using Portable body composition analyzer (InBody230, Seoul, South Korea) and Lokin Body 120 software (DMS-BIA technology; InBody Co., Seoul, South Korea) to estimate body composition, including percent of body fat (PBF), fat mass (FM), fat-free mass (FFM, kg) and skeletal muscle mass (SMM, kg). The instrument was validated against dual-energy X-ray absorptiometry for school-age children with satisfactory results for estimating body fat [ 93 ] Additional information Demographics Children’s age, gender, grade (primaries 1–6), ethnicity (Han or others), parental educational level (below college; college or above) and yearly household income (low: RMB < 84,000; medium: RMB 84,000 – 132,000; high: RMB > 132,000) [ 60 ] will be reported by parents …”
Section: Methodsmentioning
confidence: 99%